Israel-Hamas war: unspoken interests of India and China - Suryanarayana, P. S. (2024)
As champions of the rights of Palestinians, India and China see their interests entwined in the wave of unprecedented violence between Israel and Palestine’s Hamas. At the United Nations, Beijing and Delhi have differed in their voting choices on the Israel-Hamas war in Gaza. India is guided mainly by its principle of rejecting terrorism of all kinds while China has seized a strategic opportunity to woo the Palestinians and the Arab-Islamic fraternity, and to alienate them from the United States, perceivably Israel’s all-weather patron.